Implementation of Technology-Based Learning in Improving the Quality of Education at SMP IT Darul Ilmi Banyuwangi - Untung Suryadhianto; Haris Mujianto (Journal of General Education and Humanities, 2025)
This study examines the implementation of technology-based learning to improve the quality of education at SMP IT Darul Ilmi Banyuwangi. Using a qualitative case study approach, this study explores the use of technology, such as interactive multimedia, Learning Management Systems (LMS), and digital learning applications, in the teaching and learning process. These findings suggest integrating technology increases students' motivation, engagement, and understanding of learning materials. The results show that integrating technology in learning increases student motivation and engagement, but challenges such as limited technology infrastructure, unequal access to devices, and teachers' readiness to adopt technology-based learning methods are still the main obstacles. This study concludes that implementing technology-based learning has great potential to improve the quality of education, but its success depends on infrastructure readiness, teacher competence, and supportive education policies. Therefore, continuous teacher training and increased accessibility of digital devices are indispensable to ensure optimal technology implementation in education.